Penilaian Kondisi Visual Dan Prediksi Usia Sisa Jembatan Siliti Dengan Metode Bridge Management System - Adi Setiawan; Sumargo Sumargo (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
One of the efforts in bridge maintenance is by conducting a preliminary assessment with a visual assessment. Growth in the number of vehicles each time will result in a risk of decreasing the capacity of the bridge and its age. Post-construction and maintenance is also a major requirement in infrastructure. This is often ruled out causing the bridge's function and performance to decline and ultimately cause damage. Siliti Bridge is a concrete bridge located in North Bungku Morowali, Sulawesi Tengah. This bridge gets special attention due to quite severe conditions. The purpose of the inspection on the Siliti Bridge is to get its condition visually and determine the estimated age of the remaining bridge which will be capital for further inspection. Bridge Management System (BMS) is a system of assesment to know the existing condition of each element of the bridge. The condition value of the bridge is needed to calculate its remaining life. Based on evaluations conducted in 2017, the value of the Siliti Bridge using the BMS standard is 3 (Damaged). The remaining age of the Siliti Bridge is 8 years.